Koziarevych L. V. Neurolinguistic dominants of the english fascinative communication - Koziarevych L. V. (Philological Treatises, 2020)
The given article is dedicated to the English fascinative communication in the context of neurolinguistic programming. Fascinative communication is based on the concept of attracting attention. To perform an effective fascinative communication is necessary to use neuroinguistic technics.